Average hourly earnings and average weekly hours of employees paid by the hour, (SEPH), monthly - Statistics Canada (Government of Canada, 2018)
This table contains 9891 series, with data for years 1983 - 2000 (not all combinations necessarily have data for all years). This table contains data described by the following dimensions (Not all combinations are available): Geography (13 items: Newfoundland and Labrador; Canada; Nova Scotia; Prince Edward Island ...), Overtime (2 items: Including overtime; Excluding overtime ...), Estimates (2 items: Average weekly hours; Average hourly earnings ...), Standard Industrial Classification, 1980 (SIC) (283 items: Industrial aggregate excluding unclassified establishments; Logging and forestry industries; Logging industry; Goods producing industries ...), Seasonal adjustment (2 items: Unadjusted; Seasonally adjusted ...).